Small states : economic problems and prospects - Persaud, B. (OECS St John'sAG, 1987)
Considers the characteristics of small states such as their small and open economies, population, land area and per capita income,dependence on external trade and tourism, and their location in the typhoon and hurricane region. Discusses economic problems resulting from international economic forces, vulnerability to internal and external shocks, restrictions to external markets, declining aid and multilateral development assistance. Discusses prospects for economic development which are linked to technological inputs, export manufacturing, food production, and the vigour of the world economy.